Elaboración de una herramienta práctica, para el cálculo de los costos en el sector panificador de la ciudad de Duitama, con estudio particular en la Panadería Chano's - Rubiano Casallas, John Jairo (Universidad Antonio Nariño, 2021)
The purpose of the degree work is to provide a practical instrument, this is aimed at the bakery sector, which allows to obtain in a practical and timely manner the production costs incurred in each process, improving the sector's income.